How is Economic Structure Transformed? Evidence: West Kalimantan Province of Indonesia - Sartika, Nana; Sulistiawati, Rini (Faculty of Economics, Universitas Sriwijaya, 2024)
The Covid-19 pandemic caused a negative contraction in the economic structure. In West Kalimantan province, despite negative growth, the primary and secondary sectors surprisingly showed positive growth in the mining, electricity, and agriculture sectors. Based on this situation, we investigated the possibility of the structural transformation process during the pandemic. We applied Lewis's transformation theory to the analysis of primary, secondary, and tertiary sectors to examine the general trends. We used Static-Dynamic Location Quotient, Klassen typology, and Shift Share analysis, and discovered that the negative contraction in 2020 did not significantly affect each sector. However, the pattern indicates a failure in the transformation process between the tertiary and primary sectors, with the primary sector naturally proving to be the main sector in the economic structure. The critical point of our finding is that the failure of the structural transformation process was potentially caused and locked by the failure of labour shifting. To unlock the interchange of labour to modern industries, the government must address human resource issues, identify definite interchanged sectors, choose key sectors, and ensure each stage is passed thoroughlywith all necessary resources.